EFEKTIVITAS PEMANFAATAN SATELITE ASIASAT-9 UNTUK MENGATASI BLANK-SPOT (Studi Kasus pada TVRI Stasiun Sumatera Selatan) - Sukirman Sukirman; Muhammad Ridwan; Muhammad Zainal; Rika Afriani; Sri Hartati (MAP Program Pascasarjana Universitas Sjakhyakirti, 2022)
This study carefully examines the effectiveness of using the Asiasat-9 Satellite to overcome the Blank Spot in the South Sumatra Province. This study is intended to analyze and formulate how the effectiveness of the use of the Asiasat-9 Satellite to overcome the Blank Spot in the Province of South Sumatra. Research through a qualitative approach is carried out based on the problem to be studied with an explanation with the aim of exploring or building a proposition or explaining the meaning behind reality. Careful measurement of certain social phenomena is a characteristic of the descriptive level of explanation, therefore this accuracy is the basis why this study uses the descriptive level. The results of the study explained that the organization of TVRI South Sumatra has tried to be a regulator in the region in carrying out and implementing the use of the Asiasat-9 Satellite to overcome the Blank Spot in the province of South Sumatra. In an effort to support the implementation of its duties, it is necessary to support the effectiveness of the organization. Therefore, the South Sumatra Station TVRI has made efforts to increase the effectiveness of the use of the Asiasat-9 Satellite to overcome Blank Spots in the South Sumatra Province. The effectiveness level of using the Asiasat-9 Satellite to overcome Blank Spots in the South Sumatra Province for the city of Palembang is quite good, but for the Muaraenim, Lahat, Pagaralam, Ranau areas sometimes the audio and video are lost, for the TVRI program it is good, but in receiving broadcasts via Satellite Asiasat-9 if it rains Blank broadcast